Synthesis, characterization and biological evaluation of some novel fluoroquinolones - Pandit N.; Shah K.; Agrawal N.; Upmanyu N.; Shrivastava S.K.; Mishra P. (My University, 2025)
Different derivatives of fluoroquinolones were synthesized by combining it with different thiadiazoles. The synthesized compounds were characterized by infrared spectroscopy, proton nuclear magnetic resonance and mass spectral data. The compounds were screened for their antibacterial and antifungal activity. Ciprofloxacin derivatives with thiadiazoles 7c showed good antibacterial as well as antifungal activities, whereas 13c and 13e showed antibacterial and antifungal activity respectively. Sparfloxacin derivative 8c showed both antibacterial and antifungal activity. Sparfloxacin derivatives 14b and 14e showed antibacterial and antifungal activity respectively. © 2016 Springer Science+Business Media New York.